2016
DOI: 10.1038/ncomms10399
|View full text |Cite
|
Sign up to set email alerts
|

Defective DNA single-strand break repair is responsible for senescence and neoplastic escape of epithelial cells

Abstract: The main characteristic of senescence is its stability which relies on the persistence of DNA damage. We show that unlike fibroblasts, senescent epithelial cells do not activate an ATM-or ATR-dependent DNA damage response (DDR), but accumulate oxidative-stress-induced DNA single-strand breaks (SSBs). These breaks remain unrepaired because of a decrease in PARP1 expression and activity. This leads to the formation of abnormally large and persistent XRCC1 foci that engage a signalling cascade involving the p38MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 67 publications
(94 reference statements)
1
77
0
5
Order By: Relevance
“…During the aging process, the enzymes involved in DNA repair become less and less common, which increases the susceptibility of cells to genotoxic agents. 31,32 Kirsch-Volders et al 33 suggested that flaws in the cellular defense systems that protect against DNA damage, as well as the reduced efficiency of DNA repair, can lead to an accumulation of mutations. These mutations, either in isolation or in combination with other age-related alterations, can contribute to aging and the development of age-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…During the aging process, the enzymes involved in DNA repair become less and less common, which increases the susceptibility of cells to genotoxic agents. 31,32 Kirsch-Volders et al 33 suggested that flaws in the cellular defense systems that protect against DNA damage, as well as the reduced efficiency of DNA repair, can lead to an accumulation of mutations. These mutations, either in isolation or in combination with other age-related alterations, can contribute to aging and the development of age-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, sustained antioxidant treatment was sufficient to reduce the SSB level, delay senescence, and suppress post-senescence emergence. 2 In conclusion, we describe in this study a new form of senescence, which is not dependent on activation of the DDR pathway but instead dependent on activation of the SSBR pathway. This form of senescence could be the most common one occurring in vivo because it involves epithelial cells and ensues from chronic oxidative stress.…”
Section: Commentarymentioning
confidence: 57%
“…1). 2 Thus, we have revealed an unsuspected role for SSBs in senescence and demonstrated that they are an initial cause of the upregulation of p16.…”
Section: Commentarymentioning
confidence: 82%
See 2 more Smart Citations